2021
DOI: 10.1111/cxo.13068
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in primary eye care

Abstract: Optical coherence tomography angiography (OCT-A) is a non-invasive imaging modality for assessing the vasculature within ocular structures including the retina, macula, choroid and optic nerve. OCT-A has a wide range of clinical applications in various optometric conditions which have been independently reported in the literature. This paper aims to present a review of the current literature on the clinical application of OCT-A in optometric practice as well as to analyse and evaluate the quality of the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
(283 reference statements)
1
5
0
Order By: Relevance
“…OCTA is a new technique used to examine fundus lesions over recent years. This method can clearly demonstrate the morphological characteristics of superficial choroidal vessels and can quantitatively detect retinal blood flow signals [19,20]. In the present study, OCTA revealed that the SCT of the affected eyes of CSC patients was significantly thicker than that of the healthy eyes.…”
Section: Discussionsupporting
confidence: 47%
“…OCTA is a new technique used to examine fundus lesions over recent years. This method can clearly demonstrate the morphological characteristics of superficial choroidal vessels and can quantitatively detect retinal blood flow signals [19,20]. In the present study, OCTA revealed that the SCT of the affected eyes of CSC patients was significantly thicker than that of the healthy eyes.…”
Section: Discussionsupporting
confidence: 47%
“…For both RP and MD, the knowledge about alterations of small retinal vessels in the macular area is limited. Multiple degenerative retinal disorders present changes in the avascular zone and reduction in vessel density (VD) or perfusion when examined with OCT-A [9].…”
Section: Discussionmentioning
confidence: 99%
“…This 10-layer structure is shown in Figure 5A . OCTA is a non-invasive mode of retinal angiography that can not only analyze the structure of the retina but also shows the network of retinal blood vessels in vivo ( Arya et al, 2018 ; Spaide et al, 2018 ; Coffey et al, 2021 ). The inner retina is supplied with oxygen and nutrients by the central retinal artery and the outer retina by the choroidal vessels ( Kur et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%